Presence, Manifestation, and Visitation in Abrahamic Religions: The Notion of "Presence" in Shi'ism. (6th April 2022) - Asghari, Seyed Amir Hossein
Abstract: Robert Orsi's History and Presence identifies a major lacuna in the modern understanding of religion. If secularism is characteristic of the modern era, Orsi argues that it is not the absence of the faith. Instead, it is the approval of a certain kind of religion in which the "real presence, " an interaction of sacred, metaphysical realm in the everyday life of the faithful, is ignored. While considering Orsi's critique, this paper investigates the notion of presence in Shīʻī Islam along with a brief study of similar notions in Catholicism and Judaism. This paper argues that the notion of presence or ḥuḍūr plays a significant role in everyday life of Shīʻī Muslims and attempts to define it according to the context of visitation prayers and the narrations of the Shīʻī Imams. It moreover suggests that this overlooked aspect in the modern study of religion could provide grounds for a more empathetic dialogue of religions.